A study on survivin expression in prostate cancer and benign prostatic hyperplasia; and its association with pre-operative serum prostate specific antigen and gleason score in prostate cancer - Hadi, Normila Abdul (2016)
Introduction: Prostate cancer (PCa) and benign prostatic hyperplasia (BPH) are common urologic conditions in older men and both conditions are frequently coexisting. Inhibition of apoptosis has been suggested to occur in the development both conditions. The clinical significance of the survivin expression in PCa remains unclear. Objectives: The aim of this study was to determine the expression of survivin in PCa and BPH tissues; its association with Gleason score and pre-operative serum prostate specific antigen (PSA) level in PCa patients. Methods: A comparative cross-sectional study was conducted, whereby our study comprised of 159 samples obtained from archived blocks from 2009 to 2014 in Pathology Department, Hospital Universiti Sains Malaysia (HUSM). Each block was sectioned onto a single slide and stained for survivin. The expression of survivin was examined by immunohistochemistry staining. The staining was semiquantitatively scored based on both staining intensity and percentage of positive survivin cells. The percentage of positive cells and the staining intensity were multiplied to produce a weighted score for each case. The results were analysed using the Fisher exact test and Pearson χ2 test. The value of p<0.05 was considered as statistically significant. Results: A total of 91 specimens were from transrectal ultrasound (TRUS)-guided biopsy and 68 specimens were from transurethral resection of prostate (TURP). Of that, 79 specimens contained PCa tissue and 80 specimens contained BPH tissue. Survivin was expressed in all prostate specimens. However, the intensity of survivin expression in PCa are significantly greater than that in BPH (p<0.001). The distribution of nuclear and cytoplasmic positivity of survivin in PCa are significantly higher than those in BPH (p<0.001 and p=0.014 respectively). In 96.2% of PCa and 97.5% of BPH cases, the survivin was expressed in both cytoplasmic and nuclear location simultaneously. There were no significant association between intensity of survivin expression in PCa tissue with Gleason score and pre-operative serum PSA in PCa patients (p=0.474 and p>0.999 respectively). Conclusions: In this study, we report that survivin was expressed in all PCa and BPH tissues; and the expression intensity and percentage distribution of survivin positive cells were significantly greater in PCa as compared to BPH. However this study was unable to demonstrate its association with Gleason score and preoperative serum PSA in prostate cancer patients.